Numerical and polynomial modelling to assess environmental and hydraulic impacts of the future geological radwaste repository in Meuse site (France). (November 2017) - Kerrou, J.; Deman, G.; Tacher, L.; Benabderrahmane, H.; Perrochet, P.
Abstract: This study aims to evaluate the hydraulic impacts of the construction of a deep geological radwaste repository planned by the ANDRA (French National Agency for Nuclear Waste Management) within the Meuse aquifer system in the east of the Paris basin. A three-dimensional numerical model of variably-saturated flow was developed with respect to the construction data of the Underground Research Laboratory (URL). The flow calibration process was based on the Latin Hypercube Sampling of uncertain hydraulic parameters and the polynomial regression analysis of hundreds of transient flow simulations. The minimization of the objective function led to a good matching of computed and measured time series of state variables. Results showed that the flow perturbation due to the construction of the future repository extends over 10 km around the site. After an operational period of 100 years, the repository post-closure re-saturation time is estimated to thousands of years. Highlights: Development of an efficient method for groundwater flow calibration and its application to a real world case study. 3D Variably-saturated flow modelling of a complex multi-layered hydrogeological system. Development of decision making tool with regard to environmental and hydraulic impacts of the future deep geological radwaste repository in France. Long term forecast of the hydraulic impacts of the future geological radwaste repository in the next 100 years.